What determines patients' satisfaction with their mental health care and quality of life? - Blenkiron, P (BMJ Group, 2003)
Objectives: This study investigated whether patients' satisfaction with their mental health care and quality of life is related to their age, gender, psychiatric diagnosis, and duration of mental disorder. Method: 120 adults of working age who were receiving input from a community mental health team in North Yorkshire were invited to complete the Carers' and User's Expectations of Services, User Version (CUES-U) questionnaire. This 16 item self rated outcome measure covers the issues that those using mental health services have identified as being their priorities. Results: CUES-U ratings were lowest for "Social life" (49% satisfied) and highest for "Relationships with physical health workers" (88% satisfied). Satisfaction with psychiatric services correlated significantly with patients' age (Spearman's r = 0.444, p<0.001) and their satisfaction in other areas of their lives such as housing, money, and relationships (r = 0.575, p<0.001). Those with psychotic disorders rated their quality of life as higher than other respondents (median total satisfaction score 12 v 9, Mann-Whitney U = 377, p = 0.001). Gender and duration of disorder were unrelated to service satisfaction. Conclusions: Patient satisfaction ratings have been promoted as an outcome measure when evaluating the quality of their mental health services. Certain factors influencing an individual's satisfaction with the care provided (such as their age and general quality of life) are not directly under the control of professionals.